New evolutionary models for massive ZZ Ceti stars, I : first results for their pulsational properties - Althaus, Leandro Gabriel (2003)
Chaotic orbits suffer significant changes as a result of small perturbations. One can thus wonder whether the dynamical friction suffered by a satellite on a regular orbit, and interacting with the stars of a galaxy, will be different if the bulk of the stars of the galaxy are in regular or chaotic orbits. In order to check that idea, we investigated the orbital decay (caused by dynamical friction) of a rigid satellite moving within a larger stellar system (a galaxy) whose potential is nonintegrable. We performed numerical experiments using two kinds of triaxial galaxy models: (1) the triaxial generalization of Dehnen's spherical mass model (Dehnen; Merritt & Fridman); (2) a modified Satoh model (Satoh; Carpintero, Muzzio, & Wachlin). The percentages of chaotic orbits present in these models were increased by perturbing them. In the first case, a central compact object (black hole) was introduced; in the second case, the perturbation was produced by allowing the galaxy to move on a circular orbit in a logarithmic potential. The equations of motion were integrated with a non-self-consistent code. Our results show that the presence of chaotic orbits does not affect significantly the orbital decay of the satellite.